2010
DOI: 10.1111/j.1349-7006.2010.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards therapeutic antibodies to membrane oncoproteins by a robust strategy using rats immunized with transfectants expressing target molecules fused to green fluorescent protein

Abstract: Cell‐surface molecules containing growth factor receptors, adhesion molecules and transporter proteins are often over‐expressed in various cancer cells, and could be regarded as suitable targets for therapeutic monoclonal antibodies (mAb). Anti‐cancer therapeutic mAb are claimed to bind these cell‐surface molecules on viable cancer cells: therefore, it is necessary to produce mAb recognizing epitopes on the extracellular domains of native but not denatured proteins. We have experienced difficulty in obtaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 73 publications
0
46
0
Order By: Relevance
“…3A ), as described elsewhere [10], [23]. MV5 and GV5 reacted specifically with CD44R1-green fluorescent protein (GFP)-expressing cells in a GFP-expression-dependent manner; however, these mAb did not react with cells expressing CD44s-GFP, demonstrating that GV5 maintains the specificity of MV5 and specifically recognizes a human CD44R1 protein by flow cytometry (FCM).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…3A ), as described elsewhere [10], [23]. MV5 and GV5 reacted specifically with CD44R1-green fluorescent protein (GFP)-expressing cells in a GFP-expression-dependent manner; however, these mAb did not react with cells expressing CD44s-GFP, demonstrating that GV5 maintains the specificity of MV5 and specifically recognizes a human CD44R1 protein by flow cytometry (FCM).…”
Section: Resultsmentioning
confidence: 98%
“…For example, CD44R1 mRNA is elevated in human colon, bladder, lung, larynx and breast cancers [8], and immunohistological analysis (IHA) also revealed that CD44R1 protein was over-expressed in lung pleural samples compared with that in adjacent normal tissues, using rabbit polyclonal antibodies raised against recombinant CD44 protein [8]. Furthermore, we have recently demonstrated that mouse homolog of human CD44R1 is expressed in precancerous regions, possibly containing cancer stem cells (CSCs) or tumor-initiating cells, during mouse gastric carcinogenesis [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies are currently underway to further address the mechanism of CD98-mediated malignancy and resistance to cell cycle arrest and apoptosis by evaluating possible roles of CD98lc, (32,34) and by searching for novel CD98-associated molecules. (58)(59)(60) CD98hc and CD98lc (LAT1 and xCT) were overexpressed on the surface of almost all tumor cells irrespective of the tissue of origin, (26,(59)(60)(61) unlike typical receptor-type oncoproteins, such as members of the HER family with restricted tumor distribution; therefore, analysis of CD98hc-mediated transformation might reveal general mechanisms involved in the oncogenic process and might provide a novel target for cancer therapy. The significance of LAT1 in addition to CD98hc for the emergence of the malignant phenotype has been recently revealed; namely, we have demonstrated the essential role of LAT1 in malignant transformation through experimental genetics using targeted disruption of the LAT1 gene in chicken DT40 cells.…”
Section: Discussionmentioning
confidence: 99%
“…(34) Furthermore, we characterized human LAT1 as a promising target for the therapy of human cancers using experiments showing in vitro and in vivo growth inhibition of human cancer cells with hLAT1 small interfering RNA and anti-hLAT1 mAb. (34,59,61) As for novel CD98-associated molecules, we now focus on CD44 variant (CD44v) molecules expressed on the surface of cancer stem cells (CSC) in the precancerous region of gastric adenocarcinomas of K19-Wnt1/ C2mE transgenic mice. (62) Our recent data provide evidence that the expression of CD44v and its association with an xCT CD98lc block the reactive oxygen species-induced stress signaling that results in growth arrest, cell differentiation and senescence, and, thereby, promote the proliferation of cancer cells and the formation of lethal gastrointestinal tumors, (58) and that anti-CD44v fully human mAb could inhibit tumor formation or tumor growth of xenografted human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for Development of Therapeutic Monoclonal Antibodies (mAb) against the Extracellular Domain of Multi-pass Transmembrane Antigens (a) Suitable immunogens and animals for immunization to develop speciˆc mAb. Adapted from Masuko et al,14) with permission.…”
mentioning
confidence: 96%